System for the Integral Student Evaluation - Aguilera Álvarez, Duriet (2020)
The University Student Federation in Cuba carries out an important number of processes that require reducing the processing time of the information that is generated, standardizing the documentation provided by the different areas in relation to the organization, and increasing the persistence of the data. This report shows the results of the implementation of the Comprehensive Student Assessment System tool. This is a computer application that ensures the quality of the student evaluation process. It focuses mainly on the process of comprehensiveness and characterization of students, recording the trajectory of each of them in a digital file through evidence. The system was developed on the Django framework, using Python as the programming language, using PostgreSQL as the database server. To guide the entire development process of the system, the AUP-UCI methodology was used, adjusting to the technological sovereignty for which Cuba advocates. It has ten subsystems that are integrated with each other and allow the correct operation, integrity, and persistence of the data that is entered and processed. As part of the investigation, the tool is validated from different tests to the system which allowed to test the correct operation of the system and the satisfactory results of the same gave validity to the present investigation, this being the basis for the system to be able to promote student processes that take place in all universities or headquarters in the country.